Increased global posterior tibial slope is significantly associated with higher ACL graft signal intensity on 2-Year postoperative MRI after primary ACL reconstruction using hamstring tendon autografts - Zhi-yu Zhang; Le-jin Hong; Wen-bin Bai; Jia-yi Shao; Yi-tian Gao; Xiao-yue Fu; Jian-quan Wang; Cheng Wang (BMC Musculoskeletal Disorders)
Abstract Background The healing and remodeling process of tendon grafts after anterior cruciate ligament (ACL) reconstruction (ACLR) has received significant attention. This study aims to identify preoperative factors associated with postoperative signal intensity of the ACL graft after primary ACLR. Methods A total of 90 patients underwent primary ACLR using hamstring tendon autografts by the same senior surgeon between January 2013 and December 2020 were included. Patients were followed up and scheduled for a 2-year postoperative magnetic resonance imaging (MRI) scan at our institute. Concomitant injuries were confirmed by arthroscopy. Posterior tibial slope (PTS) and anterior tibial subluxation (ATS) were measured on preoperative MRI, whereas the normalized signal intensity of the ACL graft was evaluated on postoperative MRI and calculated as the ratio of the graft signal intensity to that of the patellar tendon. Multivariable linear regression models were performed to identify preoperative factors associated with the postoperative signal intensity of the ACL graft. Results Multivariable analyses showed that increased global PTS (GPTS) (P = 0.008) and concomitant articular cartilage injuries (P = 0.005) were associated with higher average signal intensity of the ACL graft on two-year postoperative MRI, while preoperative internal rotational tibial subluxation (IRTS) calculated as the difference between lateral ATS and medial ATS did not show a significant association. Specifically, an increased GPTS was significantly associated with higher signal intensity in the proximal section of the ACL graft (P = 0.005), whereas no significant associations were observed in the middle and distal sections. Conclusions Increased preoperative GPTS was significantly associated with higher signal intensity of the ACL graft on 2-year postoperative MRI after primary ACLR, suggesting that a steep preoperative tibial slope may contribute to a suboptimal ligamentization process in hamstring tendon autografts. Level of evidence Level III, retrospective cohort study.